Identity Politics in Cultural and Structural Islam in Indonesia - Ahmad Mukri Aji; Nur Rohim Yunus (Universitas Islam Negeri Jakarta, 2019)
This paper seeks to discuss the notion of identity politics in the context of Islamic identity in Indonesia. In this context, the discourse of identity politics is correlated with the concept of structural and cultural Islam, represented by the Indonesian people. In some cases, the politics of identity is often associated with intolerance and social inclusivity. The Jakarta governor election is an example when one of the candidates was a Christian Chinese and accused of committing religious blasphemy in his speech. This study concludes that both structural and cultural Islam reflect the variety of Islamic expressions, which all deserve appreciation due to the roles they have played in the development of the Muslim society. Masing-masing individu memiliki kebebasan untuk beragama di Indonesia, meskipun kebebasan itu terikat untuk tidak mengusik agama lainnya. Ketentuan ini diadopsi Negara Kesatuan Republik Indonesia dengan memberi perlindungan bagi warga negara untuk memeluk agama tanpa harus mendapat gangguan atau ancaman dari pihak manapun. Undang-Undang PNPS Nomor 1 tahun 1965 merupakan sikap negara hukum Indonesia yang tidak membiarkan pihak manapun merongrong agama resmi yang diakui negara. Fenomena yang terjadi akhir-akhir ini adalah inklusivitas sosial umat muslim yang dianggap kurang terhadap kaum minoritas. Hal ini terlihat dari sikap Muslim yang melakukan beberapa aksi protes akibat perilaku penistaan agama yang dilakukan mantan gubernur Jakarta. Dengan demikian, muncul klaim dari agama lain bahwa kaum muslim sedang melakukan politik identitas yang berdampak adanya sikap intoleransi terhadap kaum minoritas.